(untitled) (CAHIERS MAGELLANES-NS, 2024)
Guru Gobind Singh, the tenth Guru Jot of Sikhs, also known as Sant Soldier. His unique personality is not only difficult but impossible to put into words. While Guru Sahib's life is full of examples of his contribution to social progress and reforms, there are also examples of Guru Sahib's spiritual and philosophical insights. Guru Sahib tried to create the society anew from various aspects, for which Guru Sahib brought changes in the human mentality by giving practical form to the principles of the first Guru Sahib. This research paper is based on the essay 'Bhasam' written by Dr. Balbir Singh which is recorded in Shudh Sarup book, it presents the new identity given to women by Guru Gobind Singh Ji. This article is 45 pages of text that presents the testimony of Bhai Joga Singh and Kaur. At the global level, efforts have been made in various ways for women's rights, especially equality with men and women's existence. As the world has been modernized, this struggle has taken different forms. Of course, initially, these struggles were limited to legal rights, but now these efforts have taken such a form that the women's liberation movement has gone beyond legal equality or job sharing to establish the separateness of women's existence. Which has impacted the life of a man and his existence also. An alternative form of this struggle has emerged. Of course, in the early period, feminist thinkers took very commendable steps for female identity, but with time, they have also neglected the male existence to elevate the female existence. Some feminist thinkers have hypothesized that it is confusing what form the struggle should take to assert women's rights or equality. It is in these ideas that French feminist thinkers have tried to understand the mystical aspects of women's writing, women's bodies, and women's nature. (For more information see: Pardeep Kaur: 2019; 12-14) If we understand the serious aspect of this existence or identity from the context of Sikhism, then a different form emerges. Theoretically, in Gurbani, importance has been given to human existence or human life, regardless of their gender, all are equal. Both men and women have been described as the creation of the same five elements and considered the presence of God in both of them. In Gurbani, God is addressed as Purakh, and all humanity is addressed as women Jiva Nari. There is one Husband Lord, and all are His brides. (Sri Guru Granth Sahib; 933) The ideal man is described in Gurbani through the metaphor of a wife's love. How a man can please God as a husband and achieve the real purpose of life only through the qualities of a woman? For such a Gurmukh, symbols have been used in Gurbani like Suchaji, Sulakhni, Gunwanti which become Suhagan only because of their qualities. Gurmukh, i.e. one who follows the virtues of a woman, attains the grace of God. Manmukh, sitting with face turned away from God (husband), remains the most deprived. According to Gurbani, if there is a difference between human beings, it is only because of their good or bad deeds. Examples of the practical form of these principles of Gurbani can be found in the life of Guru Gobind Singh Ji and his teachings.